2011
DOI: 10.1007/s10461-011-9884-3
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk Behavior Among HIV-Infected Men Who have Sex with Men in Bangkok, Thailand

Abstract: We assessed prevalence of sexually transmitted infection (STIs), sexual risk behaviors, and factors associated with risk behaviors among HIV-infected MSM attending a public STI clinic serving MSM in Bangkok, Thailand. Between October 2005-October 2007, 154 HIV-infected MSM attending the clinic were interviewed about sexual risk behaviors and evaluated for STIs. Patients were examined for genital ulcers and had serologic testing for syphilis and PCR testing for chlamydia and gonorrhea. Results showed that sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
1
18
3
Order By: Relevance
“…Both CT and NG infections were common among Thai urban MSM; prevalence in our cohort was 19%, somewhat lower than reports from some other settings, ranging from 23% to 36% in the United Kingdom, the United States, Indonesia, and the Netherlands. 1,7,10,29,30 In our cohort, urethral infection was less prevalent than in an earlier report, 26 possibly because recruitment in Sirivongrangson et al 26 focused specifically on populations with HIV infection and those seeking treatment of symptoms of STI…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Both CT and NG infections were common among Thai urban MSM; prevalence in our cohort was 19%, somewhat lower than reports from some other settings, ranging from 23% to 36% in the United Kingdom, the United States, Indonesia, and the Netherlands. 1,7,10,29,30 In our cohort, urethral infection was less prevalent than in an earlier report, 26 possibly because recruitment in Sirivongrangson et al 26 focused specifically on populations with HIV infection and those seeking treatment of symptoms of STI…”
Section: Discussionmentioning
confidence: 64%
“…By contrast, among HIV-infected Thai MSM attending a public STI clinic in Bangkok, routine baseline screening of the urethra and rectum by NAAT in all study volunteers demonstrated CT and NG prevalence of 10% and 13%, respectively. 26 Aside from this report, information on the epidemiology, correlates, and anatomic distribution of CT and NG infection among MSM in Southeast Asia is limited.…”
mentioning
confidence: 98%
“…This varies somewhat from our sample, which was 59.4% female and 88.3% heterosexual, though, and the prevalence of HIV among MSM is lower in Chiang Mai than in the general Thai population (United Nations Program on HIV/AIDS, 2012). It has also been found that many MSM in Thailand self-identify as heterosexual or have female sexual partners (Sirivongrangson et al, 2012). Therefore, it is possible that some of the self-identified heterosexual males in our sample had past or concurrent sexual experiences with men.…”
Section: Discussionmentioning
confidence: 99%
“…Public health programs seeking to initiate contact with MSM to help those who are living with HIV/AIDS struggle to identify effective, on-theground interventions to provide care to this population. Despite the high numbers of MSM within the overall HIV epidemic in Thailand, there are few clinics that specifically aim to deliver HIV services to MSM [15]. Community-based organizations (CBOs) act as a critical link between MSM in the community and local HIV care and treatment resources.…”
Section: The Challenges Of Cbos Supporting Msm With Hiv/aids In Thailandmentioning
confidence: 99%